PENGARUH MOTIVASI DAN MENTAL KEWIRAUSAHAAN TERHADAP MINAT MAHASISWA UNTUK BERWIRAUSAHA (Studi Kasus Mahasiswa Manajemen Universitas Tridinanti Palembang) - H Hasyunah; Yusro Hakimah (JURNAL KOMPETITIF, 2020)
The influence of entrepreneurship education is one of the important factors to foster and develop potential students' interest in entrepreneurship. The purpose of this study was to determine and analyze the effect of motivation and entrepreneurial mentality partially or simultaneously on the interest in entrepreneurship at students of the Management Study Program at Tridinanti University, Palembang. The number of samples used was 467 students of Management Study Program class of 2013. Data sources obtained from the distribution of questionnaires, then analyzed using the classic assumption test, multiple regression, testing individual hypotheses (t test), F test and determinant coefficient. From the test results show that Motivation and Mental Entrepreneurship partially or simultaneously have a significant effect on Mental for Entrepreneurship in Management Study Program students, Tridinanti University, Palembang. The magnitude of the value of the coefficient of determination (Adjusted R Square) is 0.823 which implies that the magnitude of the influence of Entrepreneurial Motivation and Mentalism on Interest for Entrepreneurship is 82.3%, while the remaining 17.7% is influenced by other variables not examined in this study. Keywords:  Motivation, Mental Entrepreneurship, Interest in Entrepreneurship